The concept of hybrid molecules of tacrine and benzyl quinolone carboxylic acid (BQCA) as multifunctional agents for Alzheimer's disease - Hepnarova, V; Korabecny, J; Matouskova, L; Jost, P; Muckova, L; Hrabinova, M; Vykoukalova, N; Kerhartova, M; Kucera, T; Dolezal, R; Nepovimova, E; Spilovska, K; et al. (European journal of medicinal chemistry, 2018)
Novel tacrine-benzyl quinolone carboxylic acid (tacrine-BQCA) hybrids were designed based on multi-target directed ligands (MTLDs) paradigm, synthesized and evaluated in vitro as inhibitors of human acetylcholinesterase (hAChE) and human butyrylcholinesterase (hBChE). Tacrine moiety is represented herein as 7-methoxytacrine, 6-chlorotacrine or unsubstituted tacrine forming three different families of seven members, i.e. 21 compounds in overall. Introducing BQCA, a positive modulator of M1 muscarinic acetylcholine receptors (mAChRs), the action of novel compounds on M1 mAChRs was evaluated via Fluo-4 NW assay on the Chinese hamster ovarian (CHO-M1WT2) cell line. All the novel tacrine-BQCA hybrids were able to block the action of hAChE and hBChE in micromolar to nanomolar range. The hAChE kinetic profile of 5p was found to be mixed-type which is consistent with our docking experiments. Moreover, selected ligands were assessed for their potential hepatotoxicity on HepG2 cell line and presumable permeation through the blood-brain barrier by PAMPA assay. Expected agonistic profile towards M1 mAChRs delivered by BQCA moiety was not confirmed. From all the hybrids, 5o can be highlighted as non-selective cholinesterase inhibitor (hAChE IC50 = 74.5 nM; hBChE IC50 = 83.3 nM) with micromolar antagonistic activity towards M1 mAChR (IC50 = 4.23 μM). A non-selective pattern of cholinesterase inhibition is likely to be valuable during the onset as well as later stages of AD.
Keywords: Animals; Butyrylcholinesterase; butyrylcholinesterasa; Acetylcholinesterase; Quinolines; vztah mezi dávkou a účinkem léčiva; Positive allosteric modulator of muscarinic receptor; Multi-target directed ligands; buněčné linie; BQCA; Molecular Structure; chinoliny; Structure-Activity Relationship; lidé; Cricetulus; Cell Line; 7-Methoxytacrine; molekulární struktura; takrin; Dose-Response Relationship, Drug; Tacrine; Alzheimer's disease; acetylcholinesterasa; Alzheimer Disease; vztahy mezi strukturou a aktivitou; Alzheimerova nemoc; zvířata; cholinesterasové inhibitory; Cholinesterase Inhibitors; Acetylcholinesterase inhibitor; Humans